2019
DOI: 10.1038/s41598-019-49856-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification and injury to the inferior hypogastric plexus in nerve-sparing radical hysterectomy

Abstract: Waterjet dissection of the inferior hypogastric plexus (IHP) resulted in a more rapid return of normal urodynamics than blunt dissection (control group) in patients who received laparoscopic nerve-sparing radical hysterectomy (NSRH) in a randomized controlled study. However, the definite reasons for these results were unknown. This subgroup analysis compared the neural areas and impairment in the IHP uterine branches harvested during NSRH as an alternative to the IHP vesical branches between the waterjet and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…And the sample size included may be not enough to detect the potential differences length of parametrial tissue excised and the length of vagina. It is generally believed that a successful LNSRH results in a catheter indwelling time of about 10 days [ 43 ]. The results of this study have confirmed the effect of preserving pelvic autonomic nerves on reducing bladder dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…And the sample size included may be not enough to detect the potential differences length of parametrial tissue excised and the length of vagina. It is generally believed that a successful LNSRH results in a catheter indwelling time of about 10 days [ 43 ]. The results of this study have confirmed the effect of preserving pelvic autonomic nerves on reducing bladder dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Injuries of the hypogastric nerve may cause urinary dysfunction in female patients, and lead to incontinence (12) . Retroaortic lymph nodes should be dissected with special attention to the lumbar vessels and the affluent vein.…”
Section: Anatomy Of Nerve Structuresmentioning
confidence: 99%
“…Recently, Alsaid et al [10] showed coexistence of both parasympathetic and sympathetic fibers for both courses. Li et al [11] showed the scant paucity and the delicate nature of these neurons scattered within the IHP, consisting about 4% of the cross section. Modern investigations of the IHP underscores the significant lack of tools available to classical anatomists to understand functional neurourology.…”
Section: Autonomic Neurons and The Internal Sphinctermentioning
confidence: 99%